The Effect of Teamwork and Work Discipline on Employee Performance with Organizational Commitment as A Mediation Variable (Empirical Study at Bumi Akpelni Polytechnic Semarang) - Victor Wiku Widyo Bharoto (ProBisnis : Jurnal Manajemen, 2023)
The purpose of this research is to analyze the effect of teamwork and work discipline on employee performance with organizational commitment as a mediating variable. The population in this study were 161 employees of the Bumi Akpelni Polytechnic Semarang. Sampling in this study used a purposive judgment sampling method, 101 permanent employees were taken. Samples were taken using the census method. Data processing method using SPSS. The results of hypothesis testing show that teamwork has a positive and significant effect on organizational commitment, that the better the teamwork, the higher the organizational commitment. Work discipline has a positive and significant effect on organizational commitment. Organizational commitment has a positive and significant effect on employee performance, so employee performance is getting better. Teamwork has a positive and significant effect on employee performance, the better the teamwork, the better the employee performance. Work discipline has a positive and significant effect on employee performance, the better the work discipline applied, the better employee performance.